Synthesis of Dithiocarbamates Containing Disulfide Linkage Using Cyclic Trithiocarbonate and Amines under Solvent–Catalyst Free Condition1. (8th May 2014) - Lal, Nand; Sarswat, Amit; Kumar, Lalit; Nandikonda, Karthik; Jangir, Santosh; Bala, Veenu; Sharma, Vishnu Lal
<x xml:space="preserve">Abstract</x> A green and facile synthesis of dithiocarbamate derivatives containing disulfide linkage by the ring opening reaction of trithiocarbonate with amines under solvent and catalyst‐free condition with excellent yields is being reported. Environmental benignity, easy work up, smaller reaction time, and lack of column chromatography are the significant features of this protocol. The cyclic trithiocarbonate (1) has been used as a starting material for the first time to synthesize compounds of biological interest (3a, 3b, 3c, 3d, 3e, 3f, 3g, 3h, 3i, 3j, 3k, 3l, 3m, 3n, 3o, 3p, 3q).